The 2019 General Election in Scotland: the Issue of a Second Independence Referendum - Edwige Camp-Pietrain (Revue Française de Civilisation Britannique)
Constitutional matters were once again on the campaign agenda in Scotland in the general election held on December 12th 2019. The SNP won the election at the expense of British parties. They sought a mandate for a second independence referendum to enable the people living in Scotland to choose to remain in the UK or in the EU. However this claim was challenged, which raised questions over the way forward.